Diamond deposition in a DC-arc Jet CVD system: investigations of the effects of nitrogen addition - Smith, J; Rosser, K; Yagi, H; Wallace, M; May, P; Ashfold, M (2001)
Studies of the chemical vapour deposition of diamond films at growth rates > 100 μm h-1 with a 10-kW DC-arc jet system are described. Additions of small amounts of N2 to the standard CH4/H2/Ar feedstock gas results in strong CN(B → X) emission, and quenches C2(d → a) and Hα emissions from the plasma. Species selective, spatially resolved optical emission measurements have enabled derivation of the longitudinal and lateral variation of emitting C2, CN radicals and H (n = 3) atoms within the plasma jet. Scanning electron microscopy and laser Raman analyses indicate that N2 additions also degrade both the growth rate and quality of the deposited diamond film; the latter technique also provides some evidence for nitrogen inclusion within the films. © 2001 Elsevier Science B.V. All rights reserved.